Pola Spasial Industri Kecil Menengah (IKM) dan Industri Rumah Tangga (IRT) di Indonesia - Iluh Nadila Rahma; Darren Nataleano Metusalak Taulo; Muhammad Yasin (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The Indonesian economy is currently experiencing better and increasing economic growth. In optimizing economic development and regional growth in Indonesia, it is necessary to have an industrial spatial pattern in Small and Medium Industries and Home Industries. With the spatial pattern of industry, it can be known that the area with the highest industrial centralization and the lowest industrial concentralization area in Indonesia.